Proceedings of the 5th International Anatomical Sciences & Cell Biology Conference - Bharatham, B Hemabarathy; Masre, Siti Fathiah; Hiang Lian, Hing; Omar, Baharudin (Life Sciences, Medicine and Biomedicine, 2019)
The IASCBC 2018 provideded a platform that brings together scientists, researchers, academicians, post-graduates and experts from the fields of anatomy, microscopy and cell biology, as well as a broad range of medical, biomedical and health sciences discipline to share the current developments in their respective areas. For the first time, Malaysia hosted the much anticipated conference at the prestigious Berjaya University College at Kuala Lumpur.